Does Medical Students' Sense of Belonging Affect Their Interest in Orthopaedic Surgery Careers? A Qualitative Investigation. Issue 10 (October 2021) - Gerull, Katherine M.; Parameswaran, Priyanka; Jeffe, Donna B.; Salles, Arghavan; Cipriano, Cara A.
Abstract: Background: The concept of social belonging has been shown to be important for retention and student success in collegiate environments and general surgery training. However, this concept has never been explored in relation to medical students' impressions of orthopaedic surgery careers. Question/purpose: To investigate medical students' sense of belonging in orthopaedic surgery and how it affects their interest in pursuing orthopaedic surgery careers. Methods: Medical students from four medical schools were invited to participate in telephone interviews aimed to investigate medical students' reasons for considering (or not considering) orthopaedic surgery as a future career. Students were selected using random sampling and theoretical sampling methods (selecting participants based on specific characteristics) to obtain a diversity of student perspectives across medical school year, gender, race, age, and interest in orthopaedics. Semistructured interviews with open-ended questions and face validity were used to minimize bias in the interview process. Analysis was performed using grounded theory methodology, a rigorous and well-established method for creating conceptual models based on qualitative data. The result seeks to be a data-driven (as opposed to hypothesis-driven) theory that provides perspective on human behavior. Interviews were conducted until the point of thematic saturation, defined as the point when no new ideas occur in subsequent interviews; this was achieved at 23 students (16 self-identified as women, 12 self-identified as underrepresented minorities). Results: Medical students articulated stereotypes about orthopaedic surgeons, in particular, that they were white, male, and athletic. Students derived their sense of belonging in orthopaedic surgery from how closely their identities aligned with these stereotypes about the field. Students who felt a sense of belonging described themselves as being part of a cultural "in-group, " and students who did not feel a sense of belonging felt that they were in a cultural "out-group." Members of the in-group often reported that orthopaedic experiences further reinforced their positive identity alignment, which typically led to increased interest and continued engagement with the field. Conversely, students in the out-group reported that their exposures to orthopaedics further reinforced their lack of identity alignment, and this typically led to decreased interest and engagement. Many students in the out-group reported pursuing other specialties due to a lack of belonging within orthopaedics. Conclusion: Students derive their sense of belonging in orthopaedics based on how closely their identity aligns with stereotypes about the field. Importantly, there were gender and racial factors associated with orthopaedic stereotypes, and thus with belonging (self-identifying as the in-group). Moreover, out-group students tended not to choose orthopaedic surgery careers because of a lack of belonging in the specialty. Clinical Relevance: With knowledge of the factors that influence students' sense of belonging, academic orthopaedic departments can focus on interventions that may lead to a more diverse pool of medical students interested in orthopaedic surgery. These might include explicitly addressing stereotypes about orthopaedics and cultivating positive identity alignment for students from diverse backgrounds through targeted mentorship fostering partnerships with affinity organizations, and creating space to talk about barriers. Targeted interventions such as these are needed to interrupt the cycle of in-group and out-group formation that, in this small multicenter study, appeared to deter students with underrepresented identities from pursuing orthopaedic surgery careers.